Influence of college education on happiness: A quasi-experimental study based on higher education expansion in China - Jiang, Junfeng (Frontiers in Psychology, 2022)
Previous studies have documented a positive association between college education and happiness. However, the endogeneity of college education attainment is rarely examined, and a more robust link between college education and happiness needs to be built. Based on the Chinese General Social Survey data of 2017, the present study used the quasi-experiment of China’s higher education expansion started in 1999 to construct a fuzzy regression discontinuity design to examine the causal association between college education and happiness. It is observed that college education indeed improved Chinese happiness, but this positive association was stronger in males than in females. Further, college education was observed to improve happiness by improving individual political status, perceived social status, health and family social status, but not by increasing personal income. Accordingly, the government should continue to promote the development of higher education, and the fairness of higher education development deserves more attention to reduce population disparities in happiness.